2017
DOI: 10.1097/gox.0000000000001337
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Free Flap Reconstructions of Head and Neck Defects Due to Oral Cancer

Abstract: Objective:We studied complications following multiple free flap reconstructions in the head and neck.Methods:In this cohort, 26 patients (14 men and 12 women) who underwent multiple microvascular free flap reconstructions were included in the study. The reasons for secondary reconstruction were recurrence of tumor (12 cases), necrosis of transferred skin and/or bone (6 cases), reconstruction plate fracture or exposure (4 cases), and others (4 cases). A third reconstruction in 4 cases and a fourth reconstructio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…This makes closure of the external defect difficult, if not impossible, to reconstruct with the same flap. In these types of cases, some authors have advocated the use of two simultaneous free flaps, such as the fibula and radial forearm flap or fibula with anterolateral thigh flap combination [19]. This allows for reconstruction of all bony and soft tissue components and gives sufficient bulk for esthetics.…”
Section: Introductionmentioning
confidence: 99%
“…This makes closure of the external defect difficult, if not impossible, to reconstruct with the same flap. In these types of cases, some authors have advocated the use of two simultaneous free flaps, such as the fibula and radial forearm flap or fibula with anterolateral thigh flap combination [19]. This allows for reconstruction of all bony and soft tissue components and gives sufficient bulk for esthetics.…”
Section: Introductionmentioning
confidence: 99%
“…Thus it may be advisable to avoid the use of vessels exposed to high levels of radiation. Previous radiation may also adversely affect the success of microvascular reconstruction [35,36]. Other studies showed equivalent free flap success rates but an increased incidence of complications [37,38].…”
Section: Reconstructive Surgery After Resection For Salvagementioning
confidence: 99%
“…Reconstructive microsurgery is characterized by an emphasis on the problems of the modern techniques effectiveness in using local tissues for the restoration of extensive defects of the head, neck and upper extremities with lesions of various origins and determining the most promising directions for the development of these technologies [1,2]. A number of authors associate the occurrence of such complications as microanastomosis thrombosis, marginal flap necrosis, sub-flap suppuration, suture divergence and rejection with changes in the properties of autologous tissue after implantation and come to the conclusion that the use of musculocutaneous displaced flaps on the vascular pedicle is limited by the length of the vascular pedicle and their large thickness [2,3,4]. Free flaps on microvascular anastomoses are devoid of these drawbacks, which contributes to the wider introduction of microsurgical techniques into clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…The standard in our country and abroad is reconstructive and restorative operations, which are carried out only after the complete formation of scar tissue, i.e. 8-12 months or more after injury [2,3,4]. Injuries to the soft tissues of the head and neck, for the most part, are extensive, therefore, in order to avoid disruption of forms and functions, and the possibility of recovery with the help of local flaps, some type of regional flap is used [2,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation